Moral Distress Among Nurses Working in COVID-19 Wards: A Cross-sectional Study - Mina Pooresmail; Masoumeh Aghamohammadi (Health, Spirituality and Medical Ethics)
Background and Objectives: COVID-19 is an emerging disease, which has confronted nurses with new moral distress. This study aimed to determine the moral distress and its related factors among nurses working in the COVID-19 wards of Ardabil City, Iran. Methods: This cross-sectional descriptive study evaluated 159 nurses working in the COVID-19 wards of Imam Khomeini Hospital, the only hospitalization center for patients with COVID-19 in Ardabil, in 2021. The instruments included a personal-occupational information form and Corley’s moral distress scale (MDS). Data analysis was performed by descriptive and inferential statistics using SPSS software, version 22. Results: The mean frequency and intensity of the nurses’ moral distress were estimated at 52.28±5.24 and 51.54±5.86, respectively, which indicated a moderate level of moral distress in both dimensions. The results indicated a significant relationship between the intensity and frequency of moral distress and the type of nurses’ employment (P<0.05). Moreover, a significant relationship was observed between the nurses’ position and the frequency (P=0.04), as well as between the nurses’ work experience and the intensity of moral distress (P=0.02). Conclusion: It seems that providing the necessary training on how to deal with moral distress in new waves of the disease and using the experiences of experienced nurses in this field is essential, given the moderate level of moral distress observed among nurses working in COVID-19 wards.